1992
DOI: 10.1007/bf02541068
|View full text |Cite
|
Sign up to set email alerts
|

Dehulling of palm kernel of oil palm (Elaeis guineensis) to obtain superior‐grade palm kernel flour and oil

Abstract: A novel method has been developed for the removal of the thin, dark‐brown skin, called testa, from the palm kernel of the oil palm (Elaeis guineensis) by chemical treatment. Studies carried out for this purpose included physical or mechanical means, dry or wet heat, solvents and other chemicals. Of the procedures tried, treatment with hydrochloric acid (HCl) resulted in complete removal of the testa, producing a pearl‐white palm kernel. All other treatments were found to be ineffective. Based on our laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Hydrochloric acid treatment of the kernel was carried out as described before (Sreedhara et al 1992). BrieÑy, this consisted of treating the kernel with 4 M HCl at 95¡C for 6È7 min followed by washing the treated kernels free of acid with water and drying at 45¡C.…”
Section: Collection Of Palm Kernelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrochloric acid treatment of the kernel was carried out as described before (Sreedhara et al 1992). BrieÑy, this consisted of treating the kernel with 4 M HCl at 95¡C for 6È7 min followed by washing the treated kernels free of acid with water and drying at 45¡C.…”
Section: Collection Of Palm Kernelsmentioning
confidence: 99%
“…With the evolution of a satisfactory method for dehulling palm kernel (Sreedhara et al 1992), it has been possible to obtain pearl white kernel meal and thereby eliminating the undesirable phenolic constituents. In this connection, there appear to be no previous reports on the nutritive value of dehulled palm kernel protein (Oluwafemi 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Balogun (1982) concentró proteínas de la torta de palmiste, lo cual aumentó su digestibilidad en comparación a la torta original, con un alto potencial de mejoramiento para la alimentación animal. La remoción de la testa ha sido estudiada por Sreedhara et al (1992) que evaluó su valor nutricional para posible uso en alimentación humana.…”
Section: Introductionunclassified
“…Studies reported the possibility of chemical pre-treatment for dehulling of dent corn (Blessin et al 1970) and sesame seed (Sastry et al 1969). Sreedhara et al (1992) studied the effect of various chemical treatments (viz. hexane, methanol, chloroform, sulphuric acid, hydrochloric acid (HCl), sodium hydroxide and potassium hydroxide, phosphoric acid and acetic acid) and found that treatment with 4 N hydrochloric acid (HCl) was effective in complete removal of the testa, producing a pearl-white palm kernel.…”
mentioning
confidence: 99%